BATMAN RIBONE (Batik Malangan Triple Bottomline) Implementation Triple Bottomline for Small Medium Enterprise (SME) in Malang Regency - Siti Amerieska; Galuh Kartiko; Novi Nugrahani; Rika Wijayanti; Farika Nikmah (Journal of Community Practice and Social Welfare, 2021)
Batik Malangan craftsmen SMEs need a presence in the world of business development. The main problems faced by batik SMEs are 1) lack of good management which covers Planning, Organizing, Actuating and Controlling (POAC) as the focus of management implementation within the context of developing Batik Malangan products, 2) lack of entrepreneurial funds, 3) lack of Batik Malangan socialization (marketing), owing to the lack of web and social media presence 4) Not having financial reports, especially reports within the framework of Triple Bottom Lines (Sustainability Report). The possible solutions are in the form of assistance in the preparation of management procedure systems and the establishment of a marketplace specializing in batik products of Malang. The methods used are in the form of mentoring and training on the use of the procedure system, and the application of a web-based marketplace. The results of this community service, with the existence of Batman Ribone standard operating procedure (SOP), which contains a production planning SOP, SME owners have become increasingly aware of the importance of production planning. The existence of this web-based marketplace increased the number of customers by up to 20% and has made it easier for them to access Batik Malangan products.